Spatial Literacy through the Development of a VARK Model Based on Langkat Malay Culture Assisted by GeoGebra - Saputri, Lilis; Mardiati; Parinduri, Wina Mariana Parinduri; Franklin, Togue Nana Dipanda (RANGE: Jurnal Pendidikan Matematika, 2025)
This study aims to develop a GeoGebra-based learning model integrated with Langkat Malay local culture to enhance students' spatial literacy in geometry learning. Spatial literacy refers to students’ ability to visualize, reason geometrically, and communicate spatial ideas, which are essential for understanding mathematical concepts more deeply. The research employed a Research and Development (R&D) approach, which involved several stages including needs analysis, model design, implementation, and evaluation. The study was conducted with high school students in Langkat, North Sumatra, as research subjects. The results revealed that the integration of GeoGebra technology and local cultural elements effectively improved students’ spatial literacy. GeoGebra allowed students to explore spatial concepts visually and interactively, while the inclusion of Langkat Malay culture provided meaningful context that increased student engagement and motivation. In addition, the development of supporting materials, such as e-LKPD and GeoGebra-based practice questions, helped create a more structured and comprehensive learning environment. The study recommends teacher training on the model, further development of culturally integrated learning tools, and broader implementation in various school contexts. Future research is suggested to assess the long-term effects and explore deeper cultural integration, including local art and architecture, to strengthen students’ connection between mathematics and their cultural identity.